The psychological impact of COVID-19 on staff and patients in a psychiatric intensive care setting. (1st April 2021) - Harries, Bethan; Skelton, Luke; Blake, Lucy; Pugh, Ria; Butler, Margaret; Bolade, Adenike; Rathouse, Robert; Sethi, Faisil
This article is part of a series exploring how the COVID-19 pandemic affected, and continues to affect, a psychiatric intensive care unit (PICU) in London, UK. The series so far has focused primarily on the systems, processes and practical challenges of managing acutely disturbed patients in the inpatient setting with the added complexity of COVID-19 infection. This article outlines the psychological impact on staff and patients on a PICU during this time.